A Christian Worldview on the Humor of Jesus and Its Theological and Practical Implications - Sagala, Solomon Giftman; Salurante, Tony (International Journal of Christian Education and Philosophical Inquiry, 2025)
This study aims to further explore the dimensions of humor in Jesus' teachings and its implications for the practice of Christianity in the contemporary era. Although humor is often overlooked in a spiritual context, this study aims to further explain Jesus' humor, which functions as the most effective communication tool to convey deeper spiritual messages. In addition, through techniques such as irony, hyperbole, and parables, Jesus not only aims to entertain, but also encourages listeners to reflect on better moral values. This finding has highlighted the importance of integrating humor into the spiritual experience of Christians, which can create a more inclusive approach to forming an atmosphere of joy and laughter as an integral part of faith. Therefore, through this study, the author focuses on the importance of understanding Jesus' humor in order to improve understanding of spiritual experiences and also strengthen the bonds of the church community.